AN ANALYSIS OF EFL STUDENTS’ SPEAKING ANXIETY (A CASE STUDY AT PABUARAN 1 JUNIOR HIGH SCHOOL IN BANTEN) - SULISTYANINGSIH SULISTYANINGSIH; YUDI JUNIARDI; DINA RACHMAWATI (State University of Medan, 2024)
Studies show that speaking anxiety is a common challenge for many students of English as a Foreign Language (EFL). Therefore, this research was conducted to explore levels of speaking anxiety, factors contributing to students' anxiety, and coping strategies. Utilizing a qualitative approach with a case study design focuses on 36 eighth-grade students at SMPN 1 Pabuaran. Instruments include a close-ended questionnaire, semi-structured interview, and observational sheet, complemented by data-collecting techniques such as questionnaires, interviews, observations, and documentation. The finding reveals that 3 participants (8%) indicated high anxiety, 16 participants (45%) indicated moderate anxiety, and 17 participants (47%) indicated low anxiety. Factors contributing to anxiety include personal and interpersonal anxieties, and classroom procedures. Students employ coping strategies such as preparation, relaxation, and positive thinking. It can be inferred that students are experiencing low levels of speaking anxiety, with two main factors including personal and interpersonal anxieties and classroom procedures. The strategies employed can serve as a reference for other students in managing their anxiety and improving their speaking skills.